Arabic Language Learning Management Practices in a Non-Formal Course Institution: Evidence from At-Tasnim, Indonesia - Sriyono, Siti Amelia; Dwichandra Setyorini,; Muhammad Royan Firdaus,; Zakiyyah Salma,; Zulva Ulinnuha, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines Arabic language learning practices in a non-formal course institution through an institutional case study approach. Employing a qualitative design, the research focuses on how Arabic language learning is planned, organized, implemented, and evaluated in Lembaga Kursus Bahasa Arab (LKBA) At-Tasnim, Yogyakarta, Indonesia. Data were collected through semi-structured interviews with a key institutional actor and supported by document analysis. The findings reveal that Arabic language learning is managed as a structured and progressive process, characterized by an internally designed curriculum, a tiered learning system, flexible yet controlled implementation, and a staged evaluation mechanism oriented toward mastery of language competencies. The study also shows that institutional factors, such as organizational vision, leadership, and the integration of linguistic and religious orientations, play a central role in shaping learning practices. This research contributes to the field of Arabic language education by highlighting how non-formal institutions can organize Arabic language learning in a systematic and meaningful manner beyond formal education settings.